Effects of oxygen pressure on characteristics of 0.05Pb(Al0.5Nb0.5)O-3-0.95Pb(Zr0.52Ti0.48)O-3 thin films grown on alumina substrates by pulsed laser deposition - Kang, Min-Gyu; Cho, Kwang-Hwan; Jung, Woo Suk; Cho, Bong-Hee; Kang, Chong-Yun; Nahm, Sahn; Yoon, Seok-Jin (ELSEVIER SCIENCE SA, 2013)
Binary system of 0.05Pb(Al0.5Nb0.5)O-3-0.95Pb(Zr0.52Ti0.48)O-3 (PAN-PZT) thin films were deposited on alumina substrates by a pulsed laser deposition method and we investigated effects of oxygen pressure on ferroelectric domain structure and the piezoelectric characteristics of the films by piezoelectric force microscope (PFM). The films in optimum oxygen pressure exhibited the remnant polarization of 58.4 and 24.4 mu C/cm(2), and 180 degrees and 90 degrees domain switching behavior were observed from PFM analysis. We obtained a large effective piezoelectric constant (d(33)) value (similar to 110 pm/V) in the films. As a result, we can determine the ferroelectric domain structure and improve the piezoelectric properties of the PAN-PZT films using an oxygen pressure control during the process and it helps to obtain suitable piezoelectric thin films for sensors and actuators applications. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: ACTUATORS; IMPRINT